Clinical and Economic Consequences of Vancomycin and Fidaxomicin for the Treatment of Clostridium difficile Infection in Canada - Monika Wagner; Louis Lavoie; Mireille Goetghebeur (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Clostridium difficile infection (CDI) represents a public health problem with increasing incidence and severity.